Management, strategic management theories and the linkage with organizational competitive advantage from the resource-based view - Che Rose, Raduan; Uli, Jegak; Abdullah, Haslinda; Ismail, Alimin Ismadi (Eurojournals, 2009)
The main objective of this paper is to review the evolution of management theory, overview of strategic management theory and its linkage with the resource-based view (RBV) of the firm’s competitive advantage. A review of the relevant literature was conducted and a connection between management theory, strategic management theory and competitive advantage from the RBV of the firm was identified. It was found that the RBV of the firm’s competitive advantage is one of the main strategic management theories applicable to explain organizational performance, and it is also a part of the larger management theory family which has evolved to suit the managerial needs of the organizations and also the business environments organizations are operating in. Examining organizational competitive advantage from the RBV allows the organization to gauge the magnitude of importance placed upon its internal firm resources and capabilities in particular towards attaining a competitive advantage level, thus providing further support and extension to the RBV.